2007
DOI: 10.1089/pho.2006.990
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Exposure of Wounded Diabetic Fibroblast Cells to a Helium-Neon Laser at 5 and 16 J/cm2

Abstract: Based on cellular morphology, exposure to 5 J/cm(2) was stimulatory to cellular migration, whereas exposure to 16 J/cm(2) was inhibitory. Exposure to 16 J/cm(2) induced genetic damage on WS1 cells when exposed to a He-Ne laser in vitro, whereas exposure to 5 J/cm(2) did not induce any additional damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 15 publications
0
22
0
6
Order By: Relevance
“…23 It is described as ranging from 4 to 10 J/cm 2 for soft tissues. [35][36][37][38][39] In light of this information, the laser doses selected were 10 and 20 J/cm 2 in this investigation. Although some researchers reported that there is no relationship between the cortical bone thickness and the stability of the mini screw, [40][41][42] others reported an opposing argument.…”
Section: Discussionmentioning
confidence: 99%
“…23 It is described as ranging from 4 to 10 J/cm 2 for soft tissues. [35][36][37][38][39] In light of this information, the laser doses selected were 10 and 20 J/cm 2 in this investigation. Although some researchers reported that there is no relationship between the cortical bone thickness and the stability of the mini screw, [40][41][42] others reported an opposing argument.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to literature data indicating that adjuvant LLLT therapy reduces gingival inflammation during periodontal treatment and gives better results than basic periodontal treatment alone. 15,[35][36][37][38][39][40][41] On the side of jaws subjected to combined therapy there was no difference in nuclear area between groups, suggesting that when LLLT and basic periodontal therapy are combined, patients with DM can achieve gingival health similar to that in persons without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The alkaline comet assay indicated that 685 nm PBM delivered at energy densities above 10 J/cm 2 caused DNA damage (both SSBs and DSBs) more than 2-fold in comparison with background control levels. Previously, Houreld et al (2007) reported that after 30 minutes, a single exposure of 632.8 nm PBM at 5 J/cm 2 caused a significant increase in DNA damage [39]. However, it is not clear whether this DNA damage is completely repairable.…”
Section: Discussionmentioning
confidence: 99%